Absence of carbapenemase genes blaKPC, blaNDM and blaIMP in Escherichia coli isolated from healthy pigs from high-tech farms - Calle E., Sonia (2025)
Enterobacteriaceae is the family of bacteria with the most reports of antimicrobial resistance, with the greatest impact being those that produce carbapenems, antibiotics used in human medicine for critical cases. Various reports describe Escherichia coli as one of the carriers of these genes due to its easy uptake of plasmids or DNA fragments. In Peru, there are reports of E. coli carrying carbapenemases isolated from humans, but no confirmed work has been done in animals. Therefore, the aim of this study was to evaluate the presence of genes associated with carbapenemases in E. coli isolated from healthy pigs from four technologically advanced farms. To do this, 186 E. coli isolates were evaluated using the PCR technique for the detection of blaKPC, blaNDM and blaIMP carbapenemase genes. These genes were not detected in the 186 E. coli isolates analysed.